The Army Forces, budget and military autonomy - Soares, Samuel Alves (2007)
It is evaluated here as the relations between government and Armed Forces, and the behavior of these at the inside of the bureaucracy of State from the analysis of the federal budgets had evolved since the authoritarian government until the current one (1964-2001)- The data indicate a slow and constant decline of the expenses with the defense, larded for rises in the beginning of new governments. In general way the data suggest that the civil governments define the budgetary standard without military interference, even so the resources are used without an adequate supervision of the military activities. It is still indicated that the military autonomy, the capacity to define its field of performance, the norms that guide it and the missions to play, can be revigorated. This endemic autonomy is not originated from military choices, but from the omission of the civil power.